Antibacterial Activity of Ethanol Extract of Sirih Cina Leaves (Peperomia pellucida) Using TLC-Bioautography and Agar Diffusion Methods - Ahsan, Miftahul Khair; Herwin, Herwin; Rusli, Rusli (Fakultas Farmasi, Universitas Muslim Indonesia, 2024)
Sirih cina leaf (Peperomia pellucida) is a plant that contains active compounds of alkaloids, terpenoids, tannins, saponins, flavonoids and phenols that have potential antibacterial activity. This research aimed to determine the antibacterial activity of ethanol extract of sirih cina leaves (Peperomia pellucida) using the TLC-Bioautography and Agar Diffusion methods. Sirih cina leaf (Peperomia pellucida) was extracted by maceration and evaporated to obtain a thick extract. Screening test result showed that the extract was active at a concentration of 0.1% against the bacteria Propionibacterium acnes, Staphylococcus aureus and Pseudomonas aeruginosa. The results of antibacterial activity testing using the TLC-Bioautography method using the eluent methanol: chloroform (1:4) showed results with Rf values = 0.94, 0.80, 0.65, 0.54, 0.40, 0.30, 0.21, 0.10 against the bacteria Propionibacterium acnes, Staphylococcus aureus, and Pseudomonas aeruginosa. In determining the MIC, the value obtained was the same for the three test bacteria at a concentration of 0.5%, while the KBM value was at a concentration of 2% for Propionibacterium acnes bacteria, a concentration of 0.5% for Staphylococcus aureus bacteria, and a concentration of 1% for Pseudomonas aeruginosa bacteria. The results of antibacterial activity testing using the Agar Diffusion method obtained the largest inhibitory zone diameter at a concentration of 16% against Propionibacterium acnes bacteria with an inhibitory zone diameter of 23.20 mm, Staphylococcus aureus bacteria with an inhibitory zone diameter of 23.63 mm, and Pseudomonas aeruginosa bacteria with an inhibitory zone diameter. 24.48mm